Tabbhuwân Colo’: Tradisi Gamelan Mulut Masyarakat Nelayan Panarukan, Kabupaten Situbondo - Hidayatullah, Panakajaya (Universitas Negeri Medan, 2025)
This article examines tabbhuwân colo’, an oral gamelan tradition practiced within the fishing community of Panarukan, Situbondo. This tradition realizes the structural principles and repertoire of Madurese gending through vocal sound and the human body, without the use of metal musical instruments. Drawing on ethnographic experience gained from sitting in a circle with senior practitioners, the article approaches tabbhuwân colo’ not merely as a form of vocal art, but as a collective musical practice rooted in fishing labor, embodied memory, and the history of Madurese migration from Sumenep to the northern coast of East Java.The study employs an ethnographic approach through participant observation, in-depth interviews, and audio-visual documentation, analyzed within the theoretical frameworks of oral tradition, sound ecology, and embodiment. The findings demonstrate that tabbhuwân colo’ functions as a structured musical system, with a division of sonic roles that imitate the functions of Madurese gamelan instruments, sustained through egalitarian social coordination and collectively distributed musical knowledge. Its musical complexity does not rely on individual virtuosity, but on shared capacities for listening, mutual adjustment, and the maintenance of sonic balance. Historically, tabbhuwân colo’ developed within the context of fishing labor—particularly during the tèra’an period—and functioned as work music, a medium of social cohesion, and an archive of collective memory. However, changes in fishing technologies, the contraction of collective work spaces, and shifts in the coastal soundscape have placed this tradition in a condition of serious endangerment.